Nursing ethics: a virtue-based approach - Armstrong, Alan E. (Palgrave, 2007)
This book proposes a 'strong' (action-guiding) account of a virtue-based approach to moral decision-making within contemporary nursing practice. Merits and criticisms of obligation and virtue-based approaches to morality are explored. The author argues that in order to deliver morally good care, it is necessary to examine one's moral character